Feasibility of parent-mediated behavioural intervention for behavioural problems in children with Autism Spectrum Disorder in Nigeria: a pilot study - Bello-Mojeed, Mashudat (Child Adolesc Psychiatry Ment Health, 2016)
BACKGROUND: Autism Spectrum Disorders (ASD) is a disabling and lifelong neuro-developmental disorder. Challenging behaviours such as aggression and self injury are common maladaptive behaviours in ASD which adversely affect the mental health of both the affected children and their caregivers. Although there is evidence-base for parent-delivered behavioural intervention for children with ASD and challenging behaviours, there is no published research on the feasibility of such an intervention in sub-Saharan Africa. This study assessed the feasibility of parent-mediated behavioural intervention for challenging behaviour in children with ASD in Nigeria. METHODS: This was a pre-post intervention pilot study involving 20 mothers of children with DSM-5 diagnosis of ASD recruited from a Child and Adolescent Mental Health Service out-patient Unit. All the mothers completed five sessions of weekly manualised group-based intervention from March to April, 2015. The intervention included Functional Behavioural Analysis for each child followed by an individualised behaviour management plan. The primary outcome measure was the Aggression and Self Injury Questionnaire, which assessed both Aggression towards a Person and Property (APP) and Self Injurious Behaviour (SIB). The mothers’ knowledge of the intervention content was the secondary outcome. All outcome measures were completed at baseline and after the intervention. The mothers’ level of satisfaction with the programme was also assessed. Treatment effect was evaluated with Wilcoxon Signed Rank Tests of baseline and post-intervention scores on outcome measures. RESULTS: The children were aged 3–17 years (mean = 10.7 years, SD 4.6 years), while their mothers’ ages ranged from 32 to 52 years (mean 42.8 years, SD 6.4 years). The post intervention scores in all four domains of the APP and SIB were significantly reduced compared with pre-intervention scores. The mothers’ knowledge of the intervention content significantly increased post-intervention. The intervention was well received with the vast majority (75 %) of participants being very satisfied and all (100 %) were willing to recommend the programme to a friend whose child has similar difficulties. CONCLUSIONS: Parent-mediated behavioural intervention is a feasible and promising treatment for challenging behaviour in children with ASD in Nigeria. Behavioural intervention should be an integral component in scaling up services for children with ASD in Nigeria.